Financial support for families with children and its trade-off s balancing redistribution and parental work incentives - Michał Myck; Anna Kurowska; Michał Kundera (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Financial support for families with children implies inherent trade-offs some of which are less obvious than others. In the end these trade-offs determine the effectiveness of policy with respect to the material situation of families and employment of their parents. We analyse several kinds of trade-offs involved using a careful selection of potential changes to the system of financial support for families with children. We focus on: 1) the trade-off between redistribution of income to poorer households and improving work incentives, 2) the trade-off between improving work incentives for first and for second earners in couples, 3) the trade-off between improving work incentives for those facing strong and weak incentives in the baseline system. The exercise is conducted on data from Poland, a country characterized by high levels of child poverty, low female employment and one of the lowest fertility rates in Europe. We demonstrate the complexity of potential consequences of family support policy and stress the need for well-defined policy goals and careful analysis ahead of any reform.
Keywords: J22; J13; J18; 330; labour supply; tax and benefit reforms; microsimulation; family policy